Methods of clinical assessment from the “Clinical Recommendations” resource of the Ministry of Healthcare of Russia: a systematic review - V. M. Vatolin; O. A. Sukhorukikh; Zh. A. Galeeva; D. V. Lukyantseva; O. O. Buzuverova; O. V. Kirsanova; E. M. Murtazina; D. G. Ilyukhin; L. S. Shubina (Фармакоэкономика, 2018)
One of the key elements of medical care is the assessment of the patient’s condition, which allows making a diagnosis and evaluating the patient’s health status, the severity of the disease  and the prognosis of its outcome. To date, medical professionals use various methods of assessing the patient’s condition; these methods are listed in “Clinical Recommendations”  posted in the information resource of the Ministry of Healthcare of Russia.Objective: to analyze and systemize the many methods of clinical evaluation, e. g. scores, indices, questionnaires and other approaches that appear in the clinical guidelines.Methods. We analyzed the clinical guidelines developed by professional non-profit medical  organizations and posted on the information resource of the Ministry of Healthcare of the Russian Federation under the “Clinical Recommendations” category. A list of clinical assessment methods  derived from these guidelines was composed and potential problems in their implementation by medical organizations were identified.Results. The unified list of clinical assessments presented in the guidelines includes 175 clinical  assessment methods. The most common methods of clinical evaluation were the VAS pain score  (in 23 clinical guidelines), the Glasgow coma scale (in 11 clinical guidelines), and the ECOG scale  (in 10 clinical guidelines).Conclusion. The methods of clinical evaluation, indicated in the Minzdrav information resource  are narrowly specialized; they are used and interpreted by a physician. Some important  information about these methods and their validation is missing, which necessitates further  efforts by the medical community to improve and update these methods.